Zerumbone: a potent emerging phytochemical with anticancer therapeutic potential - Nur Aqilah Huda Ahmad Jamil,; Chong, Sylvia Hoongli; Nurul Akmaryanti Abdullah,; Noraina Mohamad Zakuan,; Hafizah Abdul Hamid,; Muhammad Zulfadli Mehat,; Manraj Singh Cheema,; Nur Fariesha Md Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Breast cancer is a prevalent cause of global mortality, characterised by abnormal cell growth within the breast. These cells can spread to distant sites in the body through metastasis and one of the mechanisms that breast cancer cells use to metastasise is via invadopodia formation. Accumulated evidence has explained pathways that may contribute to the breast cancer cells metastasis including the ERK, SMAD-3, STAT3 and NF-κB pathways. The hypoxic conditions within tumours enhance their metastatic ability through HIF-1α upregulation. Despite advanced treatments including chemotherapy and radiotherapy, these approaches are expensive and sometimes lack efficacy. Zerumbone, a compound extracted from Zingiber zerumbet, is known for its anti-cancer properties. It counteracts cancer cell metastasis by reducing cell migration, invasion, and proliferation by acting upon multiple signalling pathways. This review recapitulates the metastasis of breast cancer and its biomarkers. In addition, our review will also explore the impact of zerumbone, therapeutic roles and its mechanism of action in reducing breast cancer metastasis.